Impact of Sustainability Practices on Share Performance with Mediation of Green Innovation: A Conceptual Paper - Bhatti, Uzair; Sulaiman, Noralfishah (International Journal of Psychosocial Rehabilitation, 2020)
Corporate sustainability is now becoming an essential part of corporate business strategy. Companies in developed countries are adopting environmental, social, and economic practices to become social ambassadors. In many countries, companies that choose corporate social responsibility by adopting sustainable practices tend to have better financial performance and brand image. Many countries are rapidly adopting corporate sustainability strategies to promote green innovation. Researchers have argued that it is still considered to be a cost for the firm's investors, especially in developing countries like Malaysia. Evidence shows that these strategies show a positive sign in the company's financial performance. However, in some studies, it is still considered to be a sunk cost, particularly in the Asian region. It is challenging, if not impossible, to embed responsible behavior truly. The companies need to promote social, environmental, and economic practices that are considered to be beneficial for external investors. The paper proposes the conceptual model to understand how shareholders will respond if companies adopt sustainability practices, primarily if they invest in green innovation projects. The study is going to develop into a concrete hypothesis for future studies. This study aims to explore the impact of sustainability practices on the company's share performance through the mediation of green innovation. The model serves as a useful guide for adopting corporate sustainability practices to promote green innovation and how it will affect the firm's share performance.